2020
DOI: 10.1111/vru.12934
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional CT excretory urography is an accurate technique for diagnosis of canine ureteral ectopia

Abstract: Computed tomographic (CT) excretory urography is commonly used to investigate canine ureteral ectopia (UE). Modern technology allows time‐resolved CT imaging (four‐dimensional CT excretory urography [4D‐CTEU]) over a distance exceeding the detector collimation. Objectives of this prospective, observational, diagnostic accuracy study were to evaluate the diagnostic accuracy of CT excretory urography (CTEU) and 4D‐CTEU for UE in dogs with lower urinary tract signs, assess the influence of pelvis positioning, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 26 publications
(55 reference statements)
1
20
0
1
Order By: Relevance
“…This is similar to the previously reported sensitivity of 91% for AUS diagnosis of ureteral ectopia when compared to contrast radiography 14 . The AUS sensitivity reported in this study is similar to that of CT, lower than that of 4D‐CTEU, and greater than that of intravenous urography 10,12 . The specificity of AUS for EU has not been previously reported.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This is similar to the previously reported sensitivity of 91% for AUS diagnosis of ureteral ectopia when compared to contrast radiography 14 . The AUS sensitivity reported in this study is similar to that of CT, lower than that of 4D‐CTEU, and greater than that of intravenous urography 10,12 . The specificity of AUS for EU has not been previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…14 The AUS sensitivity reported in this study is similar to that of CT, lower than that of 4D-CTEU, and greater than that of intravenous urography. 10,12 The specificity of AUS for EU has not been previously reported. AUS has the benefit that it allows the thorough evaluation of the abdominal viscera, urinary tract, and concurrent abnormalities associated with ureteral ectopia without the requirement for a general anesthetic/heavy sedation or the administration of intravenous contrast agents.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…CTEU has been considered the imaging method of choice for the detection of ectopic ureters in dogs, 8 and in this case, it allowed to establish our final diagnosis of bilateral ectopic ureteroceles and calculus within the left one. Nevertheless, it has been recently reported that four‐dimensional CTEU is slightly superior to CTEU when investigating ureteral ectopia as cause of urinary incontinence, 10 and identification of the ureters is better visualized when the maximum intensity projection is used 11 . The treatment of ureteroceles is directed towards the preservation of renal function, preventing urinary outflow obstruction of both ureters and urinary bladder and maintaining urinary continence.…”
Section: Discussionmentioning
confidence: 99%
“…9,14 In clinical practice, the appropriate diagnostic workup is essential for establishing a correct diagnosis and prognosis and choosing the right treatment. A large number of reports have studied the diagnostic utility of radiographic, 16,22,24,30,33,34 ultrasonographic 22,[33][34][35] and CT studies 22,32,34,36,37 in dogs with urinary incontinence and ureteral ectopia. Studies supporting one diagnostic approach over another in feline patients with ureteral ectopia are unfortunately lacking.…”
Section: Discussionmentioning
confidence: 99%